2022
DOI: 10.1128/spectrum.01757-21
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mouthwash on the Oropharyngeal Microbiota of Men Who Have Sex with Men: a Substudy of the OMEGA Trial

Abstract: Given the role of the oral microbiota in human health, it is important to understand if and how external factors influence its composition. Mouthwash use is common in some populations, and the use of antiseptic mouthwash has been proposed as an alternative intervention to prevent gonorrhea transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…A previous study examining the incidence of syphilis among 96 men who have sex with men in Indonesia (2019) found that using antibacterial mouthwash containing chlorhexidine increased the odds of syphilis acquisition, and it was similarly suggested that this could be due in part to changes in the oral microbiome [ 45 ]. An Australian clinical trial has shown that daily use of Listerine or Biotene for 12 weeks had no significant effect on the oral microbiome [ 46 ]; however, no study to our knowledge has examined the effect of Betadine and Cepacol used in combination on the oral microbiome. In any event, it is clear from our interviews that, for some sex workers, mouthwash use gives the feeling of protecting against bacteria and viruses and is thus used as a safety precaution (in addition to being widely used for hygiene purposes), therefore establishing that the role of mouthwash use with regard to gonorrhea prevention is important to inform best practice.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study examining the incidence of syphilis among 96 men who have sex with men in Indonesia (2019) found that using antibacterial mouthwash containing chlorhexidine increased the odds of syphilis acquisition, and it was similarly suggested that this could be due in part to changes in the oral microbiome [ 45 ]. An Australian clinical trial has shown that daily use of Listerine or Biotene for 12 weeks had no significant effect on the oral microbiome [ 46 ]; however, no study to our knowledge has examined the effect of Betadine and Cepacol used in combination on the oral microbiome. In any event, it is clear from our interviews that, for some sex workers, mouthwash use gives the feeling of protecting against bacteria and viruses and is thus used as a safety precaution (in addition to being widely used for hygiene purposes), therefore establishing that the role of mouthwash use with regard to gonorrhea prevention is important to inform best practice.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome analysis will be undertaken as previously described 25. DNA will be extracted from tonsillar samples using the QIASymphony PowerFecal Pro kit (Qiagen).…”
Section: Discussionmentioning
confidence: 99%
“…Open access Microbiome analysis will be undertaken as previously described. 25 DNA will be extracted from tonsillar samples using the QIASymphony PowerFecal Pro kit (Qiagen). Extracted DNA will be used to generate an amplicon-based library using primers that amplify the V4 region of the 16S rRNA gene: 515F (59-GTGYCAGCMGCCGCGGTAA-39) and 806R (59-GGACTACNVGGGTWTCTAAT-39).…”
mentioning
confidence: 99%
“…After gargling the mouthwash for a week, several bacterial genera, including Prevotella , Antinomyces , and Fusobacterium , were reduced, while the genera Neisseria , Streptococcus , etc., were increased. To our best knowledge, the effects of LIS on salivary microbiome using a 16S approach have not been reported, although the long term (12 weeks) effects of LIS on oropharyngeal microbiome was recently described ( Plummer et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%